The Capacity Development of Non-Profit Organizations in the Growth Stage (An Action Research Based on the SSM) - Harry Nenobais; Azhar Kasim; Irfan Ridwan Maksum (Magister Ilmu Administrasi Publik, 2016)
This research aims in analyzing the capacity development of non-profit organizations in the growth stage through six internal components and four external components at Papuan Pesat Foundation. The approach used in the research is the action research based on the soft systems methodology that consists of two activities that had been done simultaneously, which are the research interest and the problem solving interest (McKay and Marshall, 2001). It fulfills criteria that are systematically desirable and culturally feasible (Flood an Jackson, 1991). Whilst the theory used is according to Brothers and Sherman (2012) that states that there are six internal components that should be strengthened in the growth stage, which are the leadership, the organization’s culture, the role of the board, programs’ extension, the management and infrastructure, the financial sustainable. Afterwards, according to De Vita, et. al. (2001) there are four organization’s external components that should be maintained, which are the social demographic, the economy/market, the politic and values, and the norms. The result of this research shows the research interest, that the organization needs to be equipped with the transformational leadership, the simple structure design, and the improvement of the role of the board. For the problem solving interest, it needs the working programs’ extension through the correct formulation process, the human resources management, the organization’s financial sustainability. Then the external components which need to be formed are the collaboration among the non-profit organizations, the local government, the private sectors, business activities, politic participations and the public relation.